2009
DOI: 10.2139/ssrn.1479393
|View full text |Cite
|
Sign up to set email alerts
|

Labor Market Pooling and Human Capital Investment Decisions

Abstract: Labor market pooling is considered one of the advantages of agglomerations. This paper presents a model of human capital formation in an imperfectly competitive, pooled local labor market with heterogeneous workers and firms. Firms produce with different technologies requiring diverse skills. Workers specialize into specific skills and accumulate general human capital. While labor market pooling provides static efficiency gains, our results also imply positive long-term effects: Under a diversified structure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This is due to the lower search and relocation costs incurred by firms in close proximity, and better information about new opportunities, but also because workers can leave firms that are less productive and move to firms with better productivity prospects (Combes and Duranton, 2006;Glaeser, 2010). A large pool of labour also generates benefits for firms and employees as it improves the possibility of job matches and facilitates adjustments to shocks in the local labour market (Amend and Herbst, 2009;Melo and Graham, 2014). This can enhance productivity and attract more skilled workers to the locality (Glaeser, 2010).…”
Section: Labour Market Poolingmentioning
confidence: 99%
“…This is due to the lower search and relocation costs incurred by firms in close proximity, and better information about new opportunities, but also because workers can leave firms that are less productive and move to firms with better productivity prospects (Combes and Duranton, 2006;Glaeser, 2010). A large pool of labour also generates benefits for firms and employees as it improves the possibility of job matches and facilitates adjustments to shocks in the local labour market (Amend and Herbst, 2009;Melo and Graham, 2014). This can enhance productivity and attract more skilled workers to the locality (Glaeser, 2010).…”
Section: Labour Market Poolingmentioning
confidence: 99%
“…This is, however, a condition more likely to occur when there exist multiple companies pursuing the services of similar workers (McCann et al 2011). In general, it has been indicated that the pooling of specialized employers and employees in close geographical distance also improves the overall matching process between both sides (Amend et al 2008;Otto et al 2010). This results in a pronounced labour mobility within clusters, being crucial for the inter-firm knowledge diffusion, fostering firm performance, due to the person-embedded knowledge (Erikson et al 2009;Otto et al 2010).…”
Section: Cluster Advantages and Disadvantagesmentioning
confidence: 99%